Vegetationsdynamik im Vorfeld des Lysgletschers (Valle di Gressoney/ Region Aosta/ Italien) seit 1821 - Treter, Uwe; Ramsbeck-Ullmann, Mignon; Böhmer, Hans Jürgen; Bösche, Hermann (ERDKUNDE, 2002)
After the retreat of the Lys glacier ice masses (Valle di Gressoney, Aosta Region, Italy), young larch woodland has developed on its outwash plains. The sporadic evolution of the stands after 1821, however, cannot be attributed to favourable regional climatic periods. With respect to its effect on the evolution of the woodland, the local climatic influence of the glacier overrules the influence of the regional climate. Depending on distance from the glacier, the local climatic influence can be so dominant that even the well-established individual trees react in a uniform fashion. This behaviour is reflected in predominantly synchronous tree-ring curves. The primary succession of the forest has taken place in four progressive phases. The first phase of initial shrub succession is very rich in species and characterized by high spatial diversity. In the second phase, the first tree groups become established and the development of distinct vegetation layers becomes recognisable. In the third phase, the establishment of the pioneer tree species gradually ceases. This is connected to a marked internal differentiation in the layers of the understorey. In the fourth phase, the younger forests become denser and the replacement of the pioneer species Larix decidua by Picea abies can clearly be observed. The development of the dominant pattern of the shrub-grass and cryptogame (moss/lichen) layer is mainly driven by Rhododendron ferrugineum.